IMF Survey, Volume 36 Issue 07. (IMF Survey; IMF Survey ;, 2007)
Spring Meetings focus on global growth, imbalances; IMFC communique; economic outlooks for Western Hemisphere, sub-Saharan Africa, Asia, and Europe; Aid for Lebanon's recovery; United Kingdom reaps fruits of reform; China's growth examined.